The Effect of Compensation, Job Satisfaction and Work Ability on Employee Performance at the East Medan Pratama Tax Service Office - Simbolon, Elfrida; Sitompul, Argado Vrits; Ansari, Febri; Manullang, Oyong Liza; Safrida, Safrida; Yusrita, Yusrita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of compensation, job satisfaction and work ability partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Medan Timur. Population of 95 people, and a study sample of 93 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained compensation have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by the results of t count analysis > t-table (2,938 > 1,987) at n = 93 at 95% significance level. Job satisfaction has a not effect on the performance of employees work of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count > t-table (2,128 > 1,987) at n = 93 at 95% significance level. Work ability has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by an analysis of t count >-table (3,335 > 1,987) at n = 93 with a significant level of 95%.Value of F-count > F table (16,396 > 2,71) This states that together (multiple) there are positive and significant effects of compensation, job satisfaction and work ability on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Timur.